2014
DOI: 10.1155/2014/320801
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Mechanisms ofMycoplasma pneumoniaeto Macrolide Antibiotics

Abstract: Throat swabs from children with suspected Mycoplasma pneumoniae (M. pneumoniae) infection were cultured for the presence of M. pneumoniae and its species specificity using the 16S rRNA gene. Seventy-six M. pneumoniae strains isolated from 580 swabs showed that 70 were erythromycin resistant with minimum inhibitory concentrations (MIC) around 32–512 mg/L. Fifty M. pneumoniae strains (46 resistant, 4 sensitive) were tested for sensitivity to tetracycline, ciprofloxacin, and gentamicin. Tetracycline and ciproflox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
(34 reference statements)
0
20
1
Order By: Relevance
“…Culture of M. pneumoniae was performed using PPLO (pleuropneumonia-like organisms) basic medium (BD-Difco, USA) containing 15% newborn calf serum, 10% fresh yeast extract (OXOID, UK), 0.4% phenol red indicator (Sigma, USA), 1% glucose, and 50000 U/100 mL penicillin, as described previously [21]. Tracheal swab specimens were inoculated on the M. pneumoniae liquid medium and maintained in an incubator at 37°C with a 5% CO 2 atmosphere.…”
Section: Culture Of M Pneumoniae-positive Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture of M. pneumoniae was performed using PPLO (pleuropneumonia-like organisms) basic medium (BD-Difco, USA) containing 15% newborn calf serum, 10% fresh yeast extract (OXOID, UK), 0.4% phenol red indicator (Sigma, USA), 1% glucose, and 50000 U/100 mL penicillin, as described previously [21]. Tracheal swab specimens were inoculated on the M. pneumoniae liquid medium and maintained in an incubator at 37°C with a 5% CO 2 atmosphere.…”
Section: Culture Of M Pneumoniae-positive Samplesmentioning
confidence: 99%
“…Mutations in domain V of the 23S rRNA gene are the main cause of macrolides resistance, especially those at positions 2063 and 2064. Many studies have revealed that macrolides could inhibit protein synthesis by binding to large ribosomal subunits, so mutations in 23S rRNA may lead to decreased affinity of the ribosome for drug [21]. While many reports have investigated the role of the mutation in domain V of 23S rRNA gene, no study has analyzed mutations in the ribosomal proteins L4 and L22 [36].…”
Section: Mhm170mentioning
confidence: 99%
See 1 more Smart Citation
“…Since approximately the year 2000, macrolide-resistant (MR) M. pneumoniae has been appearing in Asia, Europe, Canada, and the USA (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The rate of macrolide resistance among M. pneumoniae infections ranges from 3 to 26z in Europe (9,15), from 63 to 97z in China (16)(17)(18)(19), and from 25 to 93z in Japan (20)(21)(22). The total number of febrile days and the number of febrile days during macrolide administration are greater in patients infected with MR M. pneumoniae than in patients infected with macrolide-sensitive (MS) M. pneumoniae (23).…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasma pneumoniae (Mp) is a highly contagious and widespread human respiratory pathogen causing over 2 million cases of community-acquired pneumonia (CAP) and~100,000 adult hospitalizations annually in the United States 1 . Additionally, innate resistance to commonly used β-lactam antibiotics, increasing resistance to macrolide antibiotics, and mortality in certain demographic groups establish Mp as a high-risk pathogen capable of causing acutely severe disease [2][3][4][5][6][7] . Critically, no vaccine against Mp is available, as experimental vaccine-enhanced disease (VED) after infection has stymied further development.…”
Section: Introductionmentioning
confidence: 99%